2016
DOI: 10.1186/s12864-016-2952-3
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptional analysis suggests Lasiodiplodia theobromae pathogenicity factors involved in modulation of grapevine defensive response

Abstract: BackgroundLasiodiplodia theobromae is a fungus of the Botryosphaeriaceae that causes grapevine vascular disease, especially in regions with hot climates. Fungi in this group often remain latent within their host and become virulent under abiotic stress. Transcriptional regulation analysis of L. theobromae exposed to heat stress (HS) was first carried out in vitro in the presence of grapevine wood (GW) to identify potential pathogenicity genes that were later evaluated for in planta expression.ResultsA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 112 publications
(128 reference statements)
1
81
0
Order By: Relevance
“…Reports have shown that certain varieties are highly susceptible [ 24 , 25 ]. In vivo studies demonstrated that L. theobromae becomes aggressive in colonizing host tissues when plants are under abiotic stress, such as heat, water stress, or drought stresses [ 26 , 27 ]. In general, dieback is one of the deadly diseases of mango, which causes a serious damage to the tree and its productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that certain varieties are highly susceptible [ 24 , 25 ]. In vivo studies demonstrated that L. theobromae becomes aggressive in colonizing host tissues when plants are under abiotic stress, such as heat, water stress, or drought stresses [ 26 , 27 ]. In general, dieback is one of the deadly diseases of mango, which causes a serious damage to the tree and its productivity.…”
Section: Introductionmentioning
confidence: 99%
“…spp. were also found to be higher in other species of ascomycetes belonging to both dothideomycetes and sordariomycetes (Zhao et al 2013;Morales-Cruz et al 2015;Paolinelli-Alfonso et al 2016).…”
Section: Lignin-degrading and Lytic Polysaccharide Mono-oxygenase (Lpmo)mentioning
confidence: 81%
“…Reports have shown that certain varieties are highly susceptible [171][172]. In vivo studies demonstrated that L. theobromae becomes aggressive in colonizing host tissues when plants are under abiotic stress, such as heat, water stress, or drought stresses [173][174]. In general, dieback is one of the deadly diseases of mango, which causes serious damage to the tree and its productivity [175].…”
Section: Cause Disease Cycle and Symptomsmentioning
confidence: 99%